EFFECTIVE FORM AND METHODS OF FORMATION OF INNOVATIVE COMPETENCE IN FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
This article reveals the content and essence of the concepts of pedagogical model, pedagogical conditions, pedagogical factor. Also, the pedagogical process model aimed at forming the innovative competence of future teachers is covered in detail.